Entre grand système et alternatives d’approvisionnement en eau à Lima et La Paz - Sébastien Hardy; Jérémy Robert (EchoGéo)
Drinking water production and supply systems in the Lima and La Paz metropolis are complex. They mobilize various territories without implementing a balanced territorial solidarity. The deployment of these systems often juxtaposed is linked to the development of local hydrocracies and daily resourcing. Based on a comparison of the agglomerations of Lima and La Paz, this article proposes to analyze the characteristics and the evolutions of the systems thus highlighting a set of challenges concerning relations (often unequal) between territories and their flexibility in the face of constraints linked to climate change and urbanization dynamics.